When the State Remains Silent: Media Framing and the Politics of Femicide in Indonesia - Vellayati Hajad; Ikhsan Ikhsan; Herizal Herizal (Universitas Tribhuwana Tungga Dewi, 2026)
This study explores the intersection between media discourse and policy inaction concerning femicide in Indonesia. Despite increasing cases of lethal violence against women, the term